Analisa Optimasi Photovoltaic(PV) 100 W Menggunakan MPPT dengan Alogaritma Perturb dan Observe - Setiyawan, Puji; Utomo, Sukarno Budi; Nugroho, Agus Adhi (Elektrika, 2021)
This article reviews the optimization of energy generated by solar panels using MPPT. The need for increased power that can be done using MPPT with the P&O algorithm that goes to the load is proven because of the addition of influencing factors. MPPT A technique for keeping solar panels working. to stay within the Maximum Power point (MPP) area. MPP is a point or point in the VI curve or VP curve in the solar panel where the solar panel works at maximum efficiency and releases maximum power. The P&O algorithm is used to keep the MPPT power out panel always in the MPP area by changing the voltage value before MPPT and after the MPPT Comparison of the results of modeling with the use of techniques developed and special computer programs that have shown satisfactory results. Through comparison of the output power that comes out of the solar panel using MPPT 16.86406 W and without using MPPT of 13.63239 or experiencing an increase of 23%.